Differences in Cellular Clearing Mechanisms of Aggregates of Two Subtypes of HLA-B27 - Thakur, Amit Kumar; Luthra-Guptasarma, Manni (Frontiers in Immunology, 2022)
Ankylosing spondylitis (AS) belongs to a group of diseases, called spondyloarthropathies (SpA), which are strongly associated with the genetic marker, HLA-B27. AS is characterized by inflammation of joints, and primarily affects the spine. Over 160 subtypes of HLA B27 are known, owing to high polymorphism. Some are strongly associated with disease (e.g., B*2704) whereas others are not (e.g., B*2709). Misfolding of HLA-B27 molecules [as dimers, or as high molecular weight (HMW) oligomers] is one of several hypotheses proposed to explain the link between HLA-B27 and AS. Our group has previously established the existence of HMW species of HLA-B27 in AS patients. Still, very little is known about the mechanisms underlying differences in pathogenic outcomes of different HLA-B27 subtypes. We conducted a proteomics-based evaluation of the differential disease association of HLA B*2704 and B*2709, using stable transfectants of genes encoding the two proteins. A clear difference was observed in protein clearance mechanisms: whereas unfolded protein response (UPR), autophagy and aggresomes were involved in degradation of B*2704, the endosome-lysosome machinery was primarily involved in B*2709 degradation. These differences offer insights into the differential disease association of B*2704 and B*2709.